Investigation of the perfomance of a rotor-bearing systems containig composite and non-composite squeeze film dampers - Faris, Waleed Fekry; Khalid, Asad A.; Albagul, Abdulgani; Ismail, Godem A. (Elsevier, 2012)
In this paper, experimental vibration analysis on Teflon, woven roving glass and carbon/epoxy composite squeeze film dampers have been carried out. Composite dampers, each consists of 30 layers, were fabricated by hand lay-up method. Different outer and inner diameters of all the fabricated dampers and lengths have been used. Effect of squeeze film oil pressures of 1, 2 and 3. bar has been studied. A rotor-bearing system for the analysis has been designed and fabricated. The test rig consists of mild steel shaft, two supports, oil pressure gauge system and two self-alignment ball bearings fixed on each end support. Two squeeze film dampers were used for the two support ends. Vibration amplitude and eccentricity ratio have been examined for all the fabricated dampers at different shaft rotational speeds. The vibration amplitude and the resonance frequency are measured. The first resonance speed was examined for all the dampers tested. Results show that the vibration amplitude of the steel damper is less than carbon/epoxy, glass/epoxy and Teflon dampers. On the other hand, saving weight has been achieved by using Teflon, glass/epoxy and carbon/epoxy composite dampers. It has been found that the performance of squeeze film damper improved with increasing oil pressure and length/diameter ratio within the range tested.